Analisis Penjualan pada UMKM Es Teh Solo Cabang Kayu Putih - Apriani Hasibuan; Lala Sulastri; Dwi fika Andriani; Afifah Putri Syahrani; Salva Erena Putri; Mikhael Jasper (EKONOMIKA45 : Jurnal Ilmiah Manajemen, Ekonomi Bisnis, Kewirausahaan, 2025)
In this study, the purpose of this study is to analyze a difference in sales between the sixteen variants of the iced tea menu. The results of statistical analysis show that there is a significant difference between the average sales of the iced tea drink menu variant, with Original Sweet Tea Ice has the highest average sales. The analysis of the normality and homogeneity of the variants also showed that the menu variants had different sales characteristics. The One-Way Anova and Tukey HSD tests proved that the difference in sales between the menu variants was significant. The results of this study provide valuable insights for entrepreneurs to understand consumer behavior and increase sales by considering different marketing strategies for each menu variant.